Sex Differences in the Vasodilation Mediated by G Protein-Coupled Estrogen Receptor (GPER) in Hypertensive Rats - Delgado, Nathalie Tristão Banhos; Rouver, Wender do Nascimento; Freitas-Lima, Leandro Ceotto; Vieira-Alves, Ildernandes; Lemos, Virgínia Soares; Santos, Roger Lyrio dos (Frontiers in Physiology, 2021)
Background: The protective effect of oestrogen on the vasculature cannot be explained only by its action through the receptors ERα and ERβ. G protein-coupled oestrogen receptors (GPER) – which are widely distributed throughout the cardiovascular system – may also be involved in this response. However, little is known about GPER actions in hypertension. Therefore, in this study we evaluated the vascular response mediated by GPER using a specific agonist, G-1, in spontaneously hypertensive rats (SHR). We hypothesized that G-1 would induce a relaxing response in resistance mesenteric arteries from SHR of both sexes. Methods: G-1 concentration-response curves (1 nM-10 μM) were performed in mesenteric arteries from SHR of both sexes (10 to 12-week-old, weighing 180-250 g). The effects of G-1 were evaluated before and after endothelial removal and incubation for 30 min with the inhibitors L-NAME (300 μM) and indomethacin (10 μM) alone or combined with clotrimazole (0.75 μM) or catalase (1000 units/mL). GPER immunolocalization was also investigated, and vascular hydrogen peroxide (H2O2) and ROS were evaluated using dichlorofluorescein (DCF) and dihydroethidium (DHE) staining, respectively. Results: GPER activation promoted a similar relaxing response in resistance mesenteric arteries of female and male hypertensive rats, but with the participation of different endothelial mediators. Males appear to be more dependent on the NO pathway, followed by the H2O2 pathway, and females on the endothelium and H2O2 pathway. Conclusion: These findings show that the GPER agonist G-1 can induce a relaxing response in mesenteric arteries from hypertensive rats of both sexes in a similar way, albeit with differential participation of endothelial mediators. These results contribute to the understanding of GPER activation on resistance mesenteric arteries in essential hypertension.